Effects of Tilapia Stocking Densities on Fish Growth and Water Quality in Tanks - A.H. AL-HARBI; A.Q. SIDDIQUI (Asian Fisheries Science, 2000)
The effects of feed input and stocking density (1, 5, 10 and 15 kg.m-3 ) of hybrid tilapia (Oreochromis niloticus x O. aureus) on growth and water quality were investigated. Each density treatment was replicated three times, and stocking densities were restored by removing fish at 14-day intervals. Fish were fed a 34% protein tilapia feed to satiation within 30 min twice daily. Both feeding rates (% body weight.day-1) and percentage increase in biomass decreased significantly with increasing stocking density, but feed conversion efficiency was not significantly affected. Ammonia nitrogen, nitrite nitrogen and total phosphorus increased while DO decreased as the stocking density of fish and feed input increased. There were no significant effects of stocking densities and feed input either on nitrate nitrogen concentrations or pH of the water.